The Causal Relationship among Sustainable Development Indicators and Economic Growth – The Case of EU28 Countries - Gardiner, Richard; Hájek, Petr (Žilinská univerzita, 2016)
The concept of sustainable development can be compared to issues like democracy and globalization, because it has become a widespread contest and very important in this present time. It has compelled many authors and researchers to delve into its pillars such as social, economic and environmental likewise its indicators. The main aim of authors and researchers is characterized by finding the direction and strengths of impact among the pillars and indicators and probably come up with distinct ideas to support decision making of policy makers. Specifically, the relationship between economic growth and environmental pollution, as well as economic growth and energy consumption, has been extensively studied over the past two decades. Our study is focused on the causal relationship among the sustainable development indicators (GDP, transportation, energy consumption, and carbon emission) and their impact on economics growth in the 27 EU countries during 2005-2014. Carbon emission is regarded responsible for the majority of greenhouse gases. We use Grey models to find the relationship among the indicators. The analyses of causal relation point up the strengths and weaknesses of the sustainable development indicators (S. D. I.) on the GDP and economic growth. Based on the results the appropriate recommendation will be made.
Příčinná souvislost mezi ukazateli udržitelného rozvoje a ekonomického růstu - Případ zemí EU28
Keywords: CO2 emissions; energy consumption; transportation; GDP; CO2 emise; spotřeba energie; doprava; HDP